Huertos caseros como estrategia de seguridad alimentaria en el sector urbano San Rafael de Calceta - Carranza Delgado, Jhon Levin (2021)
The purpose of this research was to evaluate the incidence of home gardens for food security of families in San Rafael citadel located in Calceta city, Bolívar, Manabí. A quantitative descriptive study was carried out, selecting a sample of 40 families from the 52 existing in the citadel; through surveys, food insecurity was evidenced in 9 families in San Rafael citadel, which recorded higher consumption of sugar, fruits, vegetables and foods of animal origin, in addition, 31 families turned out to be middle class and 9 lower class. Prior to the implementation of the garden, 5 families were identified in the mild insecurity category, 2 in the moderate category and 2 in the severe insecurity category; while later, 5 families obtained the safe category and 4 went to the mild insecurity category. A positive incidence was evidenced in the families identified with food insecurity thanks to the training given and the elaboration of the home garden, a value of 0.90 was obtained between the variables, evidencing a correlation between good and perfect.